2020
DOI: 10.1097/md.0000000000020338
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis and visualization of medical data mining research

Abstract: Background: Data mining technology used in the field of medicine has been widely studied by scholars all over the world. But there is little research on medical data mining (MDM) from the perspectives of bibliometrics and visualization, and the research topics and development trends in this field are still unclear. Methods: This paper has applied bibliometric visualization software tools, VOSviewer 1.6.10 and CiteSpace V, to study the citation characteristics, internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 83 publications
1
23
0
3
Order By: Relevance
“…Hence, this research revealed that the United States is the most prolific country in heat health research, based on the publication output. This outcome is consistent with findings in other research fields, including sports entrepreneurship [57], climate change and infectious diseases [58], and medical data mining research [59]. Germany, which collaborates with the United States and two African countries, Nigeria and Burkina Faso, ranks second in publication output, followed by China.…”
Section: Discussionsupporting
confidence: 87%
“…Hence, this research revealed that the United States is the most prolific country in heat health research, based on the publication output. This outcome is consistent with findings in other research fields, including sports entrepreneurship [57], climate change and infectious diseases [58], and medical data mining research [59]. Germany, which collaborates with the United States and two African countries, Nigeria and Burkina Faso, ranks second in publication output, followed by China.…”
Section: Discussionsupporting
confidence: 87%
“…Data mining is a process of exploring the potential relationship between large amounts of disordered data and determining the information that may be ignored, hidden or unknown [ 27 ]. In recent years, data mining techniques have been developed rapidly in new research fields such as social network analysis, image data mining, and structural and temporal data analysis [ 28 ]. The visualization techniques transform the data mining results from abstract results into graphics or images with the help of visualization models and form rich and meaningful infographics and mapped knowledge domains, thus building a “bridge” between data mining and knowledge discovery [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…During the present information explosion, bibliometric analysis can help scientific researchers visualize knowledge structures and recognize hotspots in a research field (34)(35)(36). Our study provides the most upto-date analysis of annual publication trends, the contribution of countries, institutions, journals and authors, and the research hotspot tendencies related to disaster epidemiology from 1985 to 2020.…”
Section: Discussionmentioning
confidence: 98%